The management of chronic asthma - Fitzgerald, Mark (Henry Stewart Talks, 2013)
Importance of reviewing patient's history, Identification of potential environmental factors, Patients with uncontrolled asthma may require anti-inflammatory medications with inhaled corticosteroids (ICS) being the standard treatment, Asthmatics on ICS with uncontrolled asthma may require adjunct therapy such as a long acting beta agonist and or a leukotriene antagonist, Education program and written action plan